Preparation and evaluation of Zn(O,S) thin film layer by sulfurization method - Bahrudin M.S.; Arsad A.Z.; Abdullah S.F.; Azman N.I.; Chau C.F.; Ahmad I.; Adini W.S.W.; Mahmood Zuhdi A.W.; Wan Abdullah W.S. (Elsevier B.V., 2024)
In this paper, we propose a method of incorporating sulfur on the ZnO film surface, which can effectively alter the properties of the ZnO. Through sulfurization, a ZnS cubic crystal structure is formed in the ZnO film, with the ZnS peak increasing as the sulfur weight increases. This approach may pave the way for the successful production of Zn(O,S) film which may suit as an alternative buffer layer for CIGS solar cell structure. 2023 Elsevier B.V.